Upaya Dikmas Unit Pendidikan Dan Rekayasa Dalam Mencegah Pelanggaran Lalu Lintas Terhadap Pelajar Sma Pengguna Sepeda Motor Di Wilayah Hukum Polres Majalengka - Sarasvati, Luh Ayu Gitavira (Indonesian Journal of Police Studies, 2020)
In this millennial generation, the fact is that there is an increase in the number of these vehicles which can affect traffic life which causes traffic violations. The research objective is to determine the efforts of the Education and Engineering Unit in preventing traffic violations against high school students on motorcycle users; know the factors that cause violations, as well as obstacles in the implementation of the Dikmas Lantas. By using Management Theory as a function as a knife of analysis. The results showed the lack of effort Dikyasa Unit in providing public education to high school students. The existence of obstacles in communication also becomes a deficiency in the implementation of public education and personnel who do not yet have optimal abilities also reduce the performance of the Unit Dikyasa efforts. However, the implementation has not been optimal because of the lack of interest from students to listen to material from the Dikyasa Unit, then there are internal and external factors that support and inhibit them. For this reason, the authors suggest that the Dikyasa Unit conducts new innovations in carrying out their duties so that the implementation of the Dikmas Lantas can be well received by students optimally to achieve Kamseltibcar Lantas.